2021
DOI: 10.3390/oral1030026
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distribution in Modified Veneer Crowns: 3D Finite Element Analysis

Abstract: (1) Background: to propose a new approach for crown veneers, with the use of an aesthetic porcelain coating, only in part of the zirconia infrastructure, and to analyze its biomechanical behavior to minimize chipping failures. (2) Methods: a maxillary molar was modeled using CAD software, preparing for traditional crowns and veneer crowns with various lengths. Five groups were formed: M—control group (monolithic crown of ultra-translucent zirconia); B—conventional (bilayer crown of ultra-translucent zirconia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Because the mechanical properties between the material and the tooth tissue are different, problems may occur when exposed to load conditions such as masticatory force related to the patient's habit and finally weaken the tooth tissue to affect the survival of the tooth [28][29][30]. Several studies have investigated the materials used for restorative treatment [12][13][14][15]. However, in most of the studies, the stress distribution in the endo-crown was analyzed, and the analysis of the tooth tissue in the vital teeth was not performed [17,27,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the mechanical properties between the material and the tooth tissue are different, problems may occur when exposed to load conditions such as masticatory force related to the patient's habit and finally weaken the tooth tissue to affect the survival of the tooth [28][29][30]. Several studies have investigated the materials used for restorative treatment [12][13][14][15]. However, in most of the studies, the stress distribution in the endo-crown was analyzed, and the analysis of the tooth tissue in the vital teeth was not performed [17,27,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Ha et al [12] evaluated the stress distribution in the posterior monolithic zirconia crowns with different cement thicknesses under masticatory force and maximum bite force using three-dimensional finite element analysis. Madruga et al [13] proposed a new approach for crown veneers using an aesthetic porcelain coating only in part of the zirconia infrastructure and reported that the highly translucent zirconia ceramic only associated with the buccal covering. Ceramic could add aesthetic gain and rigidity to the system and could be a good option while restoring maxillary molars in patients who do not have parafunction.…”
Section: Introductionmentioning
confidence: 99%
“…Finite element analysis is used in dentistry in various fields: to assess the biomechanical performance of crown veneers built of zirconia [36], to assess the impact of implant abutment contact surfaces and abutment screw torque on the development of stress [37] or to assess how cement thickness affects the adhesively cemented composite inlays' polymerization shrinkage stress [38].…”
Section: Discussionmentioning
confidence: 99%